Clostridium difficile Infections in Children: Impact of the Diagnostic Method on Infection Rates. (6th June 2016) - AlGhounaim, Mohammad; Longtin, Yves; Gonzales, Milagros; Merckx, Joanna; Winters, Nicholas; Quach, Caroline
Abstract : BACKGROUND: Polymerase chain reaction (PCR) assays based on the detection of the toxin B gene are replacing enzyme-linked immunosorbent assay (ELISA)–based toxin production detection or cell cytotoxicity assay in most laboratories. OBJECTIVE: To determine the proportion of pediatric patients diagnosed with Clostridium difficile infection by PCR who would have also been diagnosed by ELISA and to compare the clinical characteristics of PCR+/ELISA+ vs PCR+/ELISA− patients. METHODS: Using the microbiology laboratory information system, stool samples positive for C. difficile by PCR between October 2010 and July 2014 were identified. Using frozen stool specimens, an ELISA for toxin A and B was performed. A retrospective medical chart review was conducted to obtain demographic and clinical data. Duplicate samples were excluded. RESULTS: A total of 136 PCR-positive samples underwent ELISA testing: 54 (40%) were positive for toxin A or B. The mean (SD) age of the entire cohort was 8.5 (6.2) years. There was no difference in age, gender, clinical manifestation, previous medical problems, and management between patients positive or negative by ELISA. However, patients positive by ELISA were more likely to have had a recent exposure to antibiotics (67.9% vs 50%; crude odds ratio, 2.1 [95% CI, 1.03–4.28]). CONCLUSION: In our pediatric population, 60% of patients with C. difficile diagnosed by PCR had no toxin detectable by ELISA. ELISA-negative patients were less likely to have received an antibiotic recently compared with ELISA-positive patients. These results highlight the need to standardize laboratory criteria for the diagnosis of C. difficile infections in children. Infect Control Hosp Epidemiol 2016;37:1087–1093